Photophysical Properties of Novel PDT Photosensitizer Radachlorin in Different Media - Vargas, Franklin; Díaz, Yrene; Yartsev, Viatcheslav; Marcano, Arístides; Lappa, Alexander (Ciencia)
The absorption and fluorescence spectra of recently presented photosensitizer for photodynamic therapy “Radachlorin” are studied in different pH, solvents and in the presence of human serum albumin. Radachlorin is found to efficiently generate singlet oxygen when irradiated with visible light. The formation of singlet oxygen by photolysis of Radachlorin was evidenced by HPLC trapping 1O2 with furfuryl alcohol and 1,3-cyclohexadiene-1,4-diethanoate and by the histidine test. The photophysical properties of this novel photosensitizer are used to discuss its anti-tumoral photoactivity.